Data Mining of Docking Results. Application to 3-Dehydroquinate Dehydratase - Boff de Avila, Mauricio; Filgueira de Azevedo Jr., Walter (Current Bioinformatics, 2014)
In this article, we describe a computational methodology that analyzes the results generated in ligand docking and evaluates the correlation between simulation results and intrinsic characteristics present in the crystallographic structures used in the simulation, such as thermal parameter, resolution, and overall quality of the X-ray diffraction data. We focus our analysis on molecular docking data obtained from application of differential evolution implemented in the program Molegro Virtual Docker. As a protein target, we selected the enzyme 3-dehydroquinate dehydratase (DHQD). This enzyme is part of the shikimate pathway, and a protein target for development of anti-tubercular drugs. We used a set with 20 DHQD crystallographic structures with ligands bound to the active site. In order to identify the best approach to molecular docking, we analyzed crystallographic parameters and looked for correlation between the docking results and structural features present in the protein target. Analysis of docking results helps to identify the best approach to use in ligand docking and identify structural features important for the success of this methodology. Analysis of results generated by ligand docking focused on DHQD made possible to assess the best docking protocol for this enzyme and use this optimized approach in the more computational demanding methodology of virtual screening (VS). We used a data set of natural products to identify structural features important for ligand-binding affinity.
Keywords: Mycobacterium tuberculosis